The impact of presenter attractiveness, video design, content vividness, and destination attractiveness on travel intentions - Fauzi Murod, Atini Rahmatika; Astuti, Rifelly Dewi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Tourism marketing trends increasingly utilize short videos to foster travel inspiration and drive travel intention. This study specifically examines the influence of presenter appeal, video design appeal, content vividness (as a new construct), and destination attractiveness on travel inspiration and its impact on travel intention. Furthermore, this study examines the mediating role of travel inspiration and openness to experience. Data were collected through an online survey of 522 respondents using purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), chosen for its ability to test complex models exploratively. The results showed that presenter attractiveness (β = 0.282; p < 0.001), video design attractiveness (β = 0.116; p = 0.019), content vividness (β = 0.118; p = 0.014), and destination attractiveness (β = 0.334; p < 0.001) significantly influenced travel inspiration, which in turn influenced travel intention (β = 0.461; p < 0.001). However, the moderating effect of openness to experience was not significant. These findings provide practical implications for tourism marketers to optimize the design of engaging, clear, and inspiring short videos to increase travel intention. Limitations of the study include the use of perceptual data and a single sample. Future research is recommended to examine additional factors and cross-cultural contexts.